A model of inflation - Cumberbatch, Cheryl Ann N. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Investigates the inflationary process in Barbados over 1961-1993 with a view to identifying a reliable model of inflation for this small open economy.